Faktor yang Berhubungan dengan Pemberian Asi Pada Bulan Pertama di Masa Pandemi Covid 19 di Kota Palangkaraya - Sukriani, Wahidah; Tabela, Ruki; Noordiati, Noordiati; Arisani, Greiny; Wahyuni, Seri (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2023)
Breastfeeding is the best way a mother can give for the baby's health. Effective breastfeeding can save 820,000 children every year. The current exclusive breastfeeding rate is far below the target set globally, nationally, and locally in Central Kalimantan Province. The highest exclusive breastfeeding was given in the first month of birth and declined with the increasing age of the baby. Based on the Indonesia health profile report, there has been a decrease in the rate of exclusive breastfeeding since the start of the COVID-19 pandemic. This study aims to determine the factors associated with breastfeeding in the first month of the COVID-19 pandemic in Palangka Raya City. This research is an analytic study with a cross-sectional design. The sample in this study was breastfeeding mothers whose babies aged > 1 month met the inclusion and exclusion criteria, as many as 97 mothers. The analysis was carried out by univariate and bivariate with a chi-square test. The results showed that only 35.1% of mothers fully breastfed their babies in the first month and there was a relationship between parity and breastfeeding in the first month during the COVID-19 pandemic (p value < 0.05). It is expected that health workers can further improve education related to breastfeeding, especially during the pandemic to increase the baby's immunity to the covid virus and improve the baby's health.